1996
DOI: 10.1093/oxfordjournals.annonc.a010602
|View full text |Cite
|
Sign up to set email alerts
|

Defining progression of ovarian carcinoma during follow-up according to CA 125: A North Thames Ovary Group study

Abstract: A confirmed rise of serum CA 125 level to more than twice the upper limit of normal during follow up after first line chemotherapy accurately predicts tumour relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
148
1
4

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(155 citation statements)
references
References 6 publications
2
148
1
4
Order By: Relevance
“…[8][9][10] And the sensitivity and specificity of PET-CT are 93.3-97.4% and 80-100%, respectively. [11,12] A recent meta-analysis of 29 studies demonstrated that PET-CT had high sensitivity (89%) and specificity (90%).…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] And the sensitivity and specificity of PET-CT are 93.3-97.4% and 80-100%, respectively. [11,12] A recent meta-analysis of 29 studies demonstrated that PET-CT had high sensitivity (89%) and specificity (90%).…”
Section: Discussionmentioning
confidence: 99%
“…Time to progression (disease-free survival) was defined as the interval from the date of treatment initiation until the disease progression was clinically evidenced by a 25% or greater increase in tumor size, appearance of new lesions, or a rise of serum CA 125 level to more than twice the upper limit of normal. 31,32 Mean time to progression was calculated as the average time from diagnosis until the date of relapse. To analyze response to primary therapy, we grouped patients as responders or non-responders to the primary therapy.…”
Section: Patient Selectionmentioning
confidence: 99%
“…The previously validated CA125 progression criteria (Rustin et al, 1996b(Rustin et al, , 2001Vergote et al, 2000) is defined as either a doubling of the CA 125 levels from the nadir value achieved during previous therapy or a doubling from the upper limit of normal. (Value defined at local laboratories.)…”
Section: Response Assessmentmentioning
confidence: 99%